2021
DOI: 10.3390/ijerph18189594
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Intermittent Foot Cooling on 1 RM Leg Press Strength in Resistance-Trained Men: A Pilot Study

Abstract: Inter-set peripheral cooling can improve high-intensity resistance exercise performance. However, whether foot cooling (FC) would increase 1 repetition maximum (RM) lower-limb strength is unclear. This study investigated the effect of intermittent FC on 1 RM leg press strength. Ten recreational male lifters performed three attempts of 1 RM leg press with FC or non-cooling (NC) in a repeated-measures crossover design separated by 5 days. FC was applied by foot immersion in 10 °C water for 2.5 min before each at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Obviously, unlike previous cooling strategies on muscles used before (Cheung and Robinson, 2004) or between (Kim and Hurr, 2020) repeated sprint-cycling workouts that did not demonstrate ergogenic effects, the intermittent application of peripheral cooling on the foot took advantage of the cooling benefits on repeated power performance. However, although a previous study demonstrated that FC increased maximal lower limb muscular force (Wu et al, 2021), contrary to expectations, peak power during cycling (i.e., ability to exert force quickly) was not affected by FC. Our findings confirm previous evidence that only mean power and not peak power is affected by various intervention strategies during repeated sprint performance and dynamic resistance exercise workouts (Frikha et al, 2020;Wilk et al, 2020).…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Obviously, unlike previous cooling strategies on muscles used before (Cheung and Robinson, 2004) or between (Kim and Hurr, 2020) repeated sprint-cycling workouts that did not demonstrate ergogenic effects, the intermittent application of peripheral cooling on the foot took advantage of the cooling benefits on repeated power performance. However, although a previous study demonstrated that FC increased maximal lower limb muscular force (Wu et al, 2021), contrary to expectations, peak power during cycling (i.e., ability to exert force quickly) was not affected by FC. Our findings confirm previous evidence that only mean power and not peak power is affected by various intervention strategies during repeated sprint performance and dynamic resistance exercise workouts (Frikha et al, 2020;Wilk et al, 2020).…”
Section: Discussioncontrasting
confidence: 85%
“…The cooling method with cold-water immersion has been applied in many studies (Cai et al, 2021;Caminita et al, 2020;Wu et al, 2021).…”
Section: Measures Fc Interventionmentioning
confidence: 99%
See 3 more Smart Citations